2019
DOI: 10.1002/ccd.28189
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibitor toxicity manifesting as comorbid Moyamoya syndrome and obstructive coronary artery disease: A case report and review of the literature

Abstract: Tyrosine kinase inhibitors (TKIs) have assumed an increasingly vital role in treating various hematologic and oncologic malignancies. However, adverse effects with respect to vascular disease have been reported following administration of this class of medications. Here, we present a case report of TKI toxicity, manifesting as comorbid Moyamoya syndrome and obstructive coronary artery disease leading to a type 1 non‐ST‐elevation myocardial infarction. This patient eventually required percutaneous coronary inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The first explanation involves potential commonalities with moyamoya disease because the present case exhibited bilateral ICA stenoses with collateral flow. Sharing similarities with TKI's antiangiogenic mechanisms, a recent report on moyamoya disease proposed that abnormal angiogenesis might be the fundamental etiology (Zhuo et al, 2019). In addition, radiological observations were also similar, as stenotic characteristics of moyamoya disease with donuts-like concentric pattern (Kim et al, 2013;Ya et al, 2020) were also reported in TKI-associated CVS (Hirschbuehl et al, 2019;Suzuki et al, 2019) and large vessel stenosis of the leg (Hirschbuehl et al, 2019), which differentiate from the typical eccentric atherosclerosis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The first explanation involves potential commonalities with moyamoya disease because the present case exhibited bilateral ICA stenoses with collateral flow. Sharing similarities with TKI's antiangiogenic mechanisms, a recent report on moyamoya disease proposed that abnormal angiogenesis might be the fundamental etiology (Zhuo et al, 2019). In addition, radiological observations were also similar, as stenotic characteristics of moyamoya disease with donuts-like concentric pattern (Kim et al, 2013;Ya et al, 2020) were also reported in TKI-associated CVS (Hirschbuehl et al, 2019;Suzuki et al, 2019) and large vessel stenosis of the leg (Hirschbuehl et al, 2019), which differentiate from the typical eccentric atherosclerosis.…”
Section: Discussionmentioning
confidence: 93%
“…Added to these similarities, some TKI-associated CVS was reported to be affected by the genetical abnormality (ring finger protein 213) of moyamoya disease (Uemura et al, 2020). Although only two reports suggested the connection to moyamoya disease in the long history of TKI (Zhuo et al, 2019;Uemura et al, 2020), future studies should focus on the etiological relationship between moyamoya disease and TKI-associated CVS. Additionally, since East Asia, including Japan, has a high prevalence of moyamoya disease, and the genetic abnormalities associated with moyamoya disease contribute to large-artery stenosis (Okazaki et al, 2019), Asian countries should exercise greater vigilance regarding cranial large arterial stenosis when using TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the patient had developed MMD secondary to underlying stroke risk factors or the previous use of TKIs known to predispose to stroke remains uncertain. The literature on the association between this medication and cardiovascular side effects is sparse [ 18 ]. However, our report highlights the potential for the drug to cause significant cardiovascular side effects.…”
Section: Discussionmentioning
confidence: 99%
“…We found one report of cocaine abuse associated with moyamoya [ 21 ]. Another two articles reported an association with nilotinib, a second-generation tyrosine kinase inhibitor [ 23 ], and bevacizumab [ 22 ].…”
Section: Reviewmentioning
confidence: 99%